A Rare Coupling: Central Tuberculous and Brucella Co-infection - Önder Durmaz; Gönül Seven Yalçın; Umut Devrim Binay; Mecdi Gürhan Balcı; Türkhun Çetin; Edhem Ünver (Current Research in MRI)
Tuberculosis and brucellosis can imitate each other in terms of clinical and laboratory findings, but their co-infection is rarely reported. The current case report will present such an uncommon co-infection. A 56-year-old farmer was admitted with complaints of disorientation and weight loss. He was infected with both tuberculosis and brucellosis. Cervical lymph node biopsy confirmed the diagnosis of tuberculosis, and hemagglutination test verified the diagnosis of brucellosis. Although tuberculous meningitis clinic is known to have a severe course, its coexistence with brucella infection should be investigated in instances that do not respond to therapy.